Potencial reprodutivo de rainhas Apis mellifera africanizadas (Hymenoptera: Apidae) ao descarte - Pereira, Vitória Alves (2023)
Understanding the quality of the queen allows for knowing information about her reproductive potential and determining the factors that influence the phenotype of the colony. Producing quality queens is an eminent demand of beekeepers, generating a large market. Surprisingly, studies need to evaluate culling queens regarding their reproductive potential, especially in commercial apiaries of Africanized honeybees, which leaves a knowledge gap. This work aimed to describe morphophysiological the queens of Africanized honeybees (Apis mellifera L.) at culling to trace their reproductive potential. One hundred and thirty-four queens were collected in commercial apiaries of the Associação de Apicultores de Capanema (APIC), with the technical support of the Brazilian Support Service for Micro and Small Companies (SEBRAE). The queens were to the Federal Technological University of Paraná, Dois Vizinhos Campus (UTFPR-DV). External measurements were performed on them, followed by dissection, evaluation of sperm quality, and histological analysis, with subsequent validation through statistics and comparison with literature. Africanized queen bees, from commercial apiaries in the Capanema region, were characterized with mean and standard deviation of total weight (183.32mg ± 22.66), full length (18.17mm ± 1.03), length (10.39 mm ± 0.93), and abdomen width (4.81mm ± 0.31), length (4.30mm ± 0.33) and thorax width (3.43 mm ± 0.43), length (10.43 mm ± 0.67) and wing width (3.60mm ± 0.30), weight of the right (30.72 mg ± 10.58) and ovary left (30.58 mg ± 10.52), the number of ovarioles in the right ovary (165.21 ± 43.57), and the left (169.58 ± 50.05), spermatheca weight (0.95mg ± 0.35). Furthermore, in the spermatecae, was found concentration of approximately 1.8 million spermatozoa, most motility was grouped in values between 0 and 40%, and sperm viability was 56.17%. Thus, in comparison with the literature of young queens it was found that the queens actually suffer wear and tear throughout their life cycle, with reduced sperm concentration, viability and motility, along with declining total weight and thorax width 20% smaller than the young. The variability found within the characteristics shows that there is room to perform selection of the Africanized queen bees. The external measures showed correlation among themselves, but there were few correlations with the morphophysiological measures, but it is noteworthy that number of ovaries showed correlation with total length (0.22) and abdomen width (0.24). Furthermore, it was verified the pressing need for the implementation of technologies in the field, especially the zootechnical control of the colonies. The database collected may encourage future research in search of the queen with better reproductive potential and successively more productive colonies.